Metformin: A therapeutic opportunity in breast cancer - Gonzalez-Angulo, Ana M. (2010)
Two important, related pathways are involved in cancer growth. The insulin/insulin-like growth factor-1 (IGF1) signaling pathway, which is activated when nutrients are available, and the adenosine mono-phosphateactivated protein kinase (AMPK) pathway, activated when cells are starved for carbohydrates. Metformin inhibits transcription of key gluconeogenesis genes in the liver, increases glucose uptake in skeletal muscle, and decreases circulating insulin levels. Metformin reduces levels of circulating glucose, increases insulin sensitivity, and reduces insulin resistance associated hyperinsulinemia. At the level of cell signaling, metformin activates AMPK. There are extensive pre-clinical data showing the anticancer effects of metformin in all breast cancer subtypes as well as in cytotoxic therapy-resistant models. These data, and the epidemiological and retrospective data supporting the antineoplastic effects of metformin, provide the rationale to study the role of metformin for breast cancer therapy in a variety of clinical settings.